2020
DOI: 10.1186/s12904-020-00620-2
|View full text |Cite
|
Sign up to set email alerts
|

“Transition from children’s to adult services for adolescents/young adults with life-limiting conditions: developing realist programme theory through an international comparison”

Abstract: Background: Managing transition of adolescents/young adults with life-limiting conditions from children's to adult services has become a global health and social care issue. Suboptimal transitions from children's to adult services can lead to measurable adverse outcomes. Interventions are emerging but there is little theory to guide service developments aimed at improving transition. The Transition to Adult Services for Young Adults with Life-limiting conditions (TAYSL study) included development of the TASYL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…A lack of engagement with adult services may result in adverse outcomes, namely, a loss of follow-up and reduced compliance with treatment, with potentially negative consequences in both the educational and social spheres [ 181 , 182 , 183 ]. In turn, poor engagement can follow inadequate preparation for the transition process while the adolescent patient is still under childhood neuropsychiatric care or unsatisfactory transition planning [ 184 , 185 ]. Thus, a healthy, planned, coordinated, patient-centered interaction between childhood neuropsychiatrists and adult healthcare professionals seems to be essential in promoting a smooth transition process and ensuring continuity of care [ 172 ].…”
Section: Raising Concern About the Transition Process: The State Of T...mentioning
confidence: 99%
“…A lack of engagement with adult services may result in adverse outcomes, namely, a loss of follow-up and reduced compliance with treatment, with potentially negative consequences in both the educational and social spheres [ 181 , 182 , 183 ]. In turn, poor engagement can follow inadequate preparation for the transition process while the adolescent patient is still under childhood neuropsychiatric care or unsatisfactory transition planning [ 184 , 185 ]. Thus, a healthy, planned, coordinated, patient-centered interaction between childhood neuropsychiatrists and adult healthcare professionals seems to be essential in promoting a smooth transition process and ensuring continuity of care [ 172 ].…”
Section: Raising Concern About the Transition Process: The State Of T...mentioning
confidence: 99%
“…Although there is not a lot of literature focused on the factors that bring about successful transition outcomes, the research that does exist suggests that key factors might include young people having experience of different jobs to help them decide what they might like to do after school (42) and good co-ordination between educational system and the labour marker (18). In transition from child to adult health services, Kerr et al (43) found validating evidence for three of the eight interventions reviewed-an early start to the transition process, developing adolescent/young adult autonomy and the role of parents/carers. The importance of effective communication between healthcare professionals and the adolescent/young adult and their parents/carers was also highlighted.…”
Section: Implications For Practicementioning
confidence: 99%
“…A páciens részére segítséget kell nyújtani a megfelelő járóbeteg-gondozó és fekvőbeteg-intézmény azonosításában. Jövőbeli kórházi ellátási igényeikre is készülni kell, azaz hogy a legmegfelelőbb szakértői központba kerülhessenek [11].…”
Section: áLtalános Célok Az áTvezetés Soránunclassified